CHARACTERIZATION SCAFFOLD 3D-PRINTING PLA WITH HYDROXYAPATITE-CHITOSAN-AgNPs COATING TO TREAT MANDIBULAR OSTEOMYELITIS - Malini, Mirza Hema; Hanan, Annisa; Ady, Jan; Aminatun (Universitas Airlangga, 2025)
Osteomyelitis The mandible can cause pathological fractures of the bones and interfere with the function of the mandible, so it is necessary to perform resection for the removal of the infected part. As a result of resection, it is necessary to carry out mandibular reconstruction using Scaffold. The study aims to discuss the effect of PLA surface modification with HA-Chitosan-AgNPs coating on morphological structure, porosity, compressive strength, hydrophilicity properties and antibacterial properties and determine the best sample variation from the characterization carried out. Scaffold made from PLA 3D-printing material using the Fused Deposition Modelling (FDM). The variation in composition (wt%) of hydroxyapatite-chitosan-AgNPs used as coatings was A (100:0:0), B (90:10:0), C (90:7:3), D (90:5:5), E (90:3:7), and F (90:0:10). The results obtained are Scaffold PLA with HA-chitosan-AgNPs coating has pores interconnected with rough surface walls. The porosity value varies between 40%-53%. HA-Kitosan-AgNPs as a surface modification are also able to increase compressive strength, antibacterial properties, and hydrophilicity Scaffold The PLA with the best sample variation is indicated by sample D (90:5:5). Based on these results, it shows that Scaffold PLA with HA-Kitosan-AgNPs coating is potentially used as a mandibular reconstruction.